Gender disparities in ADHD medication efficacy: investigating treatment outcomes for females compared to males - Davoud Amiri; Lamberto Briziarelli; Enrico Tempesta (Middle East Current Psychiatry)
Abstract Background ADHD manifests differently across genders, with females often underdiagnosed due to more internalizing symptoms such as inattention, emotional dysregulation, and anxiety. Males, in contrast, tend to display externalizing behaviors such as hyperactivity and impulsivity, leading to earlier and more frequent diagnoses. These diagnostic disparities significantly influence the efficacy and adherence to ADHD treatments across genders. Objective This narrative review investigates gender disparities in ADHD medication efficacy, focusing on the hormonal, biological, neurophysiological, and sociocultural factors influencing treatment outcomes for females compared to males. Methods Findings from 35 validated studies were synthesized, including randomized controlled trials (RCTs), observational studies, longitudinal research, systematic reviews, neuroimaging analyses, and qualitative data. Emphasis was placed on gender-specific trends in medication efficacy, adherence, side effects, and long-term outcomes. Results Hormonal fluctuations in females, such as changes in estrogen levels, influence ADHD symptom severity and medication efficacy. Evidence suggests that females may benefit more from non-stimulant treatments like atomoxetine, while stimulant medications yield more significant improvements in externalizing behaviors for boys. Gender-specific differences in treatment adherence and long-term functional outcomes are highlighted, underscoring the challenges faced by females with ADHD. Conclusion The underrepresentation of females in ADHD research skews current treatment guidelines. Addressing these gaps requires gender-inclusive studies and personalized treatment approaches that consider both biological and sociocultural differences in ADHD manifestations and treatment responses.